2009
DOI: 10.1038/npp.2009.197
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Class 1 Histone Deacetylases Reverse Contextual Memory Deficits in a Mouse Model of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized clinically by cognitive impairments that progress to dementia and death. The earliest symptoms of AD present as a relatively pure deficit in memory retrieval. Therefore, drug treatments that intervene in the early stages of AD by rescuing memory deficits could be promising therapies to slow, or even reverse progression of the disease. In this study, we tested the potential of systemic histone deacetylase inhibitor (HDACi) treatment to rescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
460
7
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 625 publications
(520 citation statements)
references
References 47 publications
39
460
7
2
Order By: Relevance
“…Female transgenic mice were used because female mice manifest an early deficit in spatial memory in the MWM test and develop greater Aβ burden compared to age‐matched male mice (Gallagher et al ., 2013). The 4.5‐month‐old mice were selected because this transgenic line develops amyloid plaque by 4–6 months of age (Yan et al ., 2009), and memory deficits as early as 6 months of age by contextual fear conditioning test (Kilgore et al ., 2010). The 4.5‐month‐old mice are suitable for investigating the effect of intranasal insulin on early Aβ pathology.…”
Section: Methodsmentioning
confidence: 99%
“…Female transgenic mice were used because female mice manifest an early deficit in spatial memory in the MWM test and develop greater Aβ burden compared to age‐matched male mice (Gallagher et al ., 2013). The 4.5‐month‐old mice were selected because this transgenic line develops amyloid plaque by 4–6 months of age (Yan et al ., 2009), and memory deficits as early as 6 months of age by contextual fear conditioning test (Kilgore et al ., 2010). The 4.5‐month‐old mice are suitable for investigating the effect of intranasal insulin on early Aβ pathology.…”
Section: Methodsmentioning
confidence: 99%
“…Indirectly enhancing histone acetylation by chronic inhibition of histone deacetylases (HDACs) was able to reverse the cognitive deficits in AD mouse model (Kilgore et al, 2010) and also in aging mouse (Benito et al, 2015). This is consistent the dysregulation of H4K12ac being implicated to mediate cognitive impairment in aged mice (Peleg et al, 2010).…”
Section: Molecular Links Between Aging and Admentioning
confidence: 99%
“…Among these, APP/PS1 double transgenic mice are an extensively used model, showing progressive age-related development of Aβ accumulation and cognitive deficits (Jankowsky et al 2001;Trinchese et al 2004;van Groen et al 2006;Meyer-Luehmann et al 2009;Filali et al 2011;Janus et al 2015). Furthermore, previous studies have revealed positive results, such as demonstrating various antioxidants (Garcia-Alloza et al 2010;Varamini et al 2014;Yanagisawa et al 2015), neuroprotective agents (Kilgore et al 2010;Peng et al 2012;Li et al 2014), anti-neuroinflammation (Cherry et al 2015;Guo et al 2015), immune therapy (Sudduth et al 2013;Carrera et al 2013;Zhang et al 2015), and nonpharmacological interventions (Liu et al 2011;Jankowsky et al 2005), which can attenuate or even reserve AD-like pathology in APP/PS1 mice. Unfortunately, none of these potentially useful results have been able to be reproduced in clinical therapies for AD patients.…”
Section: Introductionmentioning
confidence: 99%